The Influence of Personality on Job Satisfaction At PT. Surya Windu Pertiwi Serdang Bedagai - Nanda Putra; Risa Kartika Lubis (Junal Ilmu Manajemen, 2021)
This study aims to analyze personality, job satisfaction and the influence of personality on job satisfaction of employees of PT Surya Windu Pertiwi Serdang Bedagai. Respondents in this study were employees of PT Surya Windu Pertiwi Serdang Bedagai consisting of 43 respondents. The data analysis method used is descriptive statistics and simple regression. The results of the test show that the personality of openees to experience is a prominent personality of the employees of PT Surya Windu Pertiwi Serdang Bedagai with an average score of 3.8889. Meanwhile, the average value of descriptive statistics for the job satisfaction variable was 3.1457, indicating that the employees of PT Surya Windu Pertiwi Serdang Bedagai still did not have good job satisfaction. The results of the analysis show that personality does not have a positive and significant effect on job satisfaction of employees with a P-value of 0.382 greater than 0.05. The managerial implication that can be given is that companies need to consider the factors of employee personality, especially when recruiting employees. Companies also need to consider aspects of job satisfaction, especially in terms of good salaries